Inhibition of histone deacetylases accelerates wound healing in diabetic skin and is associated with vascularization and epidermal tight junction protein expression - Juan Valentin Trujillo-Paez; Adrián Rodríguez-Carlos; Nancy Solís-Torres; Yessica E. Félix-García; Irma González-Curiel; Luis Adrián De Jesús-González; Crisol Rodriguez Mendieta; César Rivas-Santiago; Bruno Rivas-Santiago (Tissue and Cell, 2027)

Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Detection of Sarcocystis aucheniae DNA in placental and umbilical cord tissues suggests possible vertical transmission in domestic South American camelids - Monica Florin-Christensen; Juan Reategui-Ordoñez; Cesar Vargas Tacuri; Luisa Neyra; Carlos V. Enriquez; Evelyn Diaz; Halley Rodriguez Huanca; Ximena Barriga Marcapura; Luis V.M. Olivera; Susana M. Giuliano (Veterinary Parasitology, 2026)

When things go wrong: The detrimental interplay of environmental factors on bioturbation in a Jurassic shallow-marine system from western Argentina - Debora M. Campetella; Maximiliano N. Rodriguez; Juan José Ponce; Ainara Irastorza; Martin N. Rogel; Noelia B. Carmona; Nerina Canale; Luis A. Buatois; M. Gabriela Mángano (Journal of South American Earth Sciences, 2026)

ALVO: a collective platform for volcanic risk reduction in Latin America - Pablo Forte; Daniel Bertin; Lizzette Rodriguez; Mariana Patricia Jácome Paz; Silvana Hidalgo; Yemerith Alpizar-Segura; Guillermo E. Alvarado; Constanza Perales Moya; José Luis Palma; José G. Viramonte; Hugo Delgado-Granados (Journal of South American Earth Sciences, 2026)

The resident effect dominates over previous winner/loser experience in surface fish of the Mexican tetra - Julian Navarro-Pagan; Paola Figueroa-Colon; Alexander Figueroa-Negron; Luis Perez-Fabregat; Antonio Morales-Cintrón; Jean Mendoza-Anduce; Alondra Ortiz-Franco; Robert A. Kozol; Roberto Rodriguez-Morales (Animal Behaviour, 2026)

Regional patterns of environmental variability in mangrove ecosystems along the southeastern Brazilian coast - Marcelo Antonio Amaro Pinheiro; Luis Felipe de Almeida Duarte; Caio Rodrigues Nobre; Esli Emanoel Domingues Mosna; Rodrigo dos Santos Rodriguez-Lopes; Todor Petkov; Aleksandar Dimitrov; Dimitrinka Ivanova (Regional Studies in Marine Science, 2026)

Clinical predictors, microbiological profile, and outcomes of bacteremia in patients with cellulitis: a 6-year retrospective cohort study - Ana Cotos Suárez; Amparo López-Bernus; Montserrat Alonso-Sardón; Virginia Velasco Tirado; Laura Sancha Domínguez; Beatriz Rodriguez Alonso; Josue Pendones Ulerio; Juan Luis Muñoz Bellido; Moncef Belhassen-García (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Background Cellulitis is a common cause of hospital admission, yet the clinical relevance and predictors of bacteremia remain incompletely characterized. Identifying patients at risk of bloodstream infection may help optimize diagnostic strategies and clinical management. Methods We conducted a retrospective observational study at a tertiary-care hospital including all consecutive patients hospitalized with cellulitis between January 2019 and December 2024. Patients without blood cultures were excluded. Clinical severity was stratified using the CREST classification. Microbiological data, antibiotic therapy, hospital outcomes, and follow-up at 1 and 3 months were analyzed. Results Among 311 episodes included, bacteremia was confirmed in 46 cases (14.8%). Patients with bacteremia showed significantly higher clinical severity at admission, with CREST grades III–IV present in 56.5% compared with 36.6% in non-bacteremia patients ( p < 0.001). Sepsis occurred in 65.2% of bacteremia cases versus 24.5% of non-bacteremia cases ( p < 0.001). Bacteremia was associated with longer hospital stay (18 ± 18.3 vs 13 ± 9.7 days; p = 0.003) and more frequent antibiotic modifications during admission ( p = 0.023). Streptococcal species and Staphylococcus aureus showed a higher propensity for bloodstream invasion. In-hospital mortality was higher among bacteremia patients (13.0% vs 7.9%), although the difference was not statistically significant. Three-month mortality reached 14.3% in the bacteremia group compared with 9.9% in non-bacteremia patients. Conclusion Bacteremia complicating cellulitis is uncommon but associated with greater clinical severity, longer hospitalization, and increased therapeutic complexity. Severity stratification tools such as CREST may assist in identifying patients at increased risk of bacteremia; however, given their limited discriminatory performance, they should not be used in isolation to guide blood culture collection or other clinical decisions.

Temporal patterns of neotropical psittacids at the mascoitania clay lick in the manu biosphere reserve, Peru - Carolina Milagros Herrera-Huayhua; Javier Amaru-Castelo; Renato Walter Colan-Rodriguez; Emma Achahuanco-Sallo; Edgar Luis Marquina-Montesinos (Ornithology Research, 2026)

Machine learning-enhanced strategies for detecting modified and emerging mycotoxins: Advances and future directions - Xiyu He; Jieqiang Liu; Tong Yu; Zulipikaer Rouzi; Zhongkun Zhang; Luis Rodriguez-Saona; Yang Suo; Baima Yangjin; Aerna Yeerjiang; Min Wu; Xian Zhang; Baoshu Liu; et al. (Trends in Food Science & Technology, 2026)

Development of an ELISA as a complement to MAT for swine leptospirosis diagnosis - Micaela Esteban; Cristina Sanchez; Marcelo A. Rodriguez; Vanina R. Saraullo; Micaela Hamer; Bibiana F. Brihuega; Luis Samartino; Mara L. Martinez (Research in Veterinary Science, 2026)

Relationships between gluten proteins and texture in low-hydration dough - Jeffrey Eiseman; Byung-Kee Baik; Osvaldo Campanella; Luis E. Rodriguez-Saona; Emmanuel Hatzakis (Food Research International, 2026)

Influence of dietary linoleic acid inclusion on fatty acid composition in barrows and gilts and its relationship to fat accumulation - Deysi Guevara-Freire; Rosa M. Escudero; Luis Calvo; Ana I. Rodriguez; Raquel Reina; José Ignacio Morales; Álvaro Olivares; Clemente López-Bote (Meat Science, 2026)

Effects of Fishmeal Substitution with House Cricket Meal (Acheta domesticus) on Productive Performance and Nutrient Metabolism of Blue Tilapia (Oreochromis aureus) - Aldo Fraijo-Valenzuela; Joe Luis Arias-Moscoso; Francisco Cadena-Cadena; Barbara Aboites-Martínez; Ramón Casillas-Hernández; Libia Zulema Rodriguez-Anaya; Pablo Gortáres-Moroyoqui; Jose Reyes Gonzalez-Galaviz (Fishes, 2026)
A 10-week feeding experiment was conducted to evaluate the effects of replacing fishmeal with cricket meal on the productive performance and transcriptional responses of genes related to nutrient metabolism and growth of blue tilapia (Oreochromis aureus). Five conventional tilapia feeds were formulated to replace fishmeal with cricket meal. Control diet (CD) was formulated with 20% fishmeal, and four diets gradually replaced fishmeal with cricket meal at 20, 40, 60, and 80% (D1–D4). A total of 200 fingerling tilapia (2.00 ± 0.09 g) were randomly distributed into 20 tanks (10 fish/tank), with four replicates per dietary treatment. The results showed that fish fed CD and D1 had higher growth performance values than those fed D2–D4. The feed conversion ratio (FCR) was significantly better in fish fed CD and D1 compared with fish fed D2–D4. The survival rate was similar for all treatments. The transcriptional response of genes related to nutrient digestion, absorption, and transport; lipid metabolism; and the somatotropic axis was marked downregulated in fish fed D2 and D4, whereas in fish fed D3, it exhibited a unique compensatory regulation across most pathways, likely sustained by its higher dietary lipid content. Although cricket meal did not prevent the metabolic effects associated with high soybean meal inclusion, survival remained high across all treatments. Cricket meal can replace up to 20% of the fishmeal in the feed for blue tilapia fingerlings, with soybean meal as the main protein source.

Beneficial and potentially harmful compounds in edible mushrooms cultivated on substrates supplemented with algal wracks from Mar Menor lagoon seashore - Sara Figueredo; Rebeca Lavega; Luis Vázquez; Carlos García-Delgado; Francisco R. Marin; Alejandro Ruiz-Rodriguez; Cristina Soler-Rivas (Biocatalysis and Agricultural Biotechnology, 2026)

Impact of volcanic emissions on the air quality during the 2021 volcanic eruption of Tajogaite, La Palma: Implications for population exposure to volcanic pollutants - Julia Eychenne; Raphael Paris; Agnès Borbon; David Jessop; Mathieu Gouhier; Guillem Gisbert Pinto; Antoni Calafat; Aurélie Colomb; José-Luis Fernandez-Turiel; Vincent Gaussen; Clara Gorce; Séverine Moune; et al. (Science of The Total Environment, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Advancing smart detection of pesticide residues in food through machine learning-enhanced vibrational spectroscopy techniques - Siyu Yao; Tong Yu; Alessandra Fantina Victorio Ramos; Zhongkun Zhang; Luis Rodriguez-Saona (Food Chemistry, 2026)

Correction to: The influence of grain size and channelization on mobility of volcanic granular flows: insights from laboratory experiments - Roberto Sulpizio; Sara Meschiari; Damiano Sarocchi; Francesco Neglia; Luis Angel Rodriguez-Sedano; Federico Lucchi; Oscar Segura-Cisneros; Fabio Dioguardi; Bernardino Barrientos (Bulletin of Volcanology, 2026)

Molecular responses to pollution stress in glass eels (Anguilla anguilla): Gene expression changes associated with varying contamination levels and temperature across estuaries - Alvaro Gutierrez-Rodriguez; Claudia Nuñez-Moyano; Lucía Rivas-Iglesias; Susana Acle; Luis Jose Royo-Martin; Eva Garcia-Vazquez; Gonzalo Machado-Schiaffino (Aquatic Toxicology, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Genetic diversity of Mycoplasma bovis isolated from bovine respiratory disease and bovine mastitis in Chile - Matías Goddard; Joscelyn San Martín; Jose Arturo Molina-Mora; Luis Collado; Jaime Rodriguez; Nicolás Galarce; Armin Mella (Veterinary Microbiology, 2025)

Sex-based differences in rainbow trout innate immunity: in vivo and in vitro gene expression - Yubing Chen; Anitha Bhat; Olivia Hou-Ling Dixon; Jesús Luis Betancourt; Tania Rodriguez-Ramos; Brian Dixon (Fish & Shellfish Immunology, 2025)

Probiotic Potential of Yeast, Mold, and Intermediate Morphotypes of Geotrichum candidum in Modulating Gut Microbiota and Body Physiology in Mice - Madeeha Gohar; Nida Shaheen; Sagar M. Goyal; Sunil Kumar Mor; Luis M. Rodriguez-R; Muhammad Imran (Probiotics and Antimicrobial Proteins, 2025)

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

The influence of grain size and channelization on mobility of volcanic granular flows: insights from laboratory experiments - Roberto Sulpizio; Sara Meschiari; Damiano Sarocchi; Francesco Neglia; Luis Angel Rodriguez-Sedano; Federico Lucchi; Oscar Segura-Cisneros; Fabio Dioguardi; Bernardino Barrientos (Bulletin of Volcanology, 2025)
Laboratory experiments on granular flows using natural material were carried out under different conditions in order to investigate the behavior of fine to coarse-grained, channelized and non-channelized granular flows passing over a break in slope. Morphometric parameters of channelized and non-channelized experiments are compared for both fine-grained and coarse-grained grain size distributions. After normalization, morphometric data provide empirical relationships that highlight the major influence of grain size vs. channelization of the experimental flows. Normalized velocity data of the flow front show third-order polynomial fit for both coarse-grained and fine-grained experiments, as well as for non-channelized and channelized ones. This highlights similar complex behavior of the different experimental flows, which differs only for different partition of inertial and frictional forces at changing grain size of experimental mixtures. The runout of coarse-grained granular flows is always longer than that of fine-grained granular flows, irrespective if they are channelized or non-channelized. Finally, we discuss the applicability of the experimental results to natural granular flows, highlighting the change in physical behavior of fine-rich pyroclastic density currents and volcaniclastic flows depending on the effectiveness of fluidization processes in fine-grained natural materials.

Response of sympatric species of tinamous (Tinamidae) to a disturbance gradient in a secondary forest in the Manu Biosphere Reserve, Peru - Luis Antonio Echevarria-Macassi; Renato Walter Colan-Rodriguez; Javier Amaru-Castelo; Edgar Luis Marquina-Montesinos (Ornithology Research, 2025)

“Effects of mercury exposure in three Amazonian agricultural plant species and the impact on bacterial population in soil” - Maria J. Rodriguez-Pascual; Claudia Vega; Natasha Andrade; Luis E. Fernández; Shih-Huai Cheng; Birthe Kjellerup; Alba Torrents (Environmental Research, 2025)

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

Ex vivo assessment of potential Eucalyptus cinerea antihypertensive - Daniela Yusbizareth Rodriguez-Jimenez; Samuel Enoch Estrada-Soto; Luis Arias-Duran; Gabriela Maria Avila-Villarreal (Phytochemistry Letters, 2025)

Disease prevalence in confiscated exotic and indiginous birds and reptiles housed in a cites-authorized rescue center in Spain - M. Jimenez Martinez; A. Martin; A. Rabanal Soto; V. Hidalgo Martinez; A. Rodriguez Luis; M. Aranda Vazquez; J. De Andres Gamazo (Journal of Comparative Pathology, 2025)

A cross-dimensional analysis of data-driven short-term load forecasting methods with large-scale smart meter data - Han Li; Miguel Heleno; Wanni Zhang; Kaiyu Sun; Luis Rodriguez Garcia; Tianzhen Hong (Energy and Buildings, 2025)

Mechanisms and Therapeutic Potential of Key Anti-inflammatory Metabiotics: Trans-Vaccenic Acid, Indole-3-Lactic Acid, Thiamine, and Butyric Acid - Muñoz-Olivos Cristina; Bautista-Rodriguez Elizabeth; Rivas-Arreola María Jose; Palacios-Gonzalez Berenice; Zacapa Diego; Cortez-Sanchez Jose Luis (Probiotics and Antimicrobial Proteins, 2025)

Resin: not only a secondary forest product - Martin Delgado-Rodriguez; Roque Rodríguez-Soalleiro; Silvana Ribeiro Nobre; Luiz Carlos Estraviz Rodriguez; Luis Diaz-Balteiro (European Journal of Forest Research, 2025)
Given the lack of studies focusing on the economic aspects of pine forests with resin production objectives, this study has analysed the economically optimal rotation age and profitability of two forest plantations that are commonly used for resin production in their respective countries: Slash pine in Brazil and Maritime pine in Spain. The scope of the two case studies encompassed resin, timber production and carbon sequestration, assuming that the latter could be traded in voluntary markets. An initial conservative assumption was made that resin can be picked only three years before final felling. The main objective was to demonstrate whether the economically optimal rotation varies with the introduction of resin and carbon, and whether the profitability of resin is comparable to that of timber. Additionally, an alternative scenario was considered wherein resin tapping was allowed for a prolonged period. The results have demonstrated that the integration of provisioning (resin and wood) with regulating (carbon) ecosystem services significantly increases profitability compared to the option of timber production alone, while the optimal rotation age is modified to a much lesser extent. It is also concluded that, at least in some situations, resin production should not be considered a secondary or complementary product to timber production. Furthermore, it is imperative to emphasize the need for appropriate silvicultural models to manage these three products jointly.

Assessing anthropogenic microfiber pollution in the southwestern Atlantic Ocean: a large-scale study on spatial distribution, concentration, and physical characterization - Rosana Di Mauro; Nadia Marina Alves; Julieta Rodriguez; Lucila Sobrero; Ignacio Luis Chiesa; Constanza Hozbor; Lucrecia Allega; Julieta Antacli; Marina Vera Díaz; Agustín Schiariti (Environmental Science and Pollution Research, 2025)

A practical guide on environmental genomics for prokaryotic systematics - Nathan M. Ernster; Luis M. Rodriguez-R (Systematic and Applied Microbiology, 2025)

A mathematical model for strategic management of the forest supply chain considering its products and energy generation - Salomé Rodriguez; Diego Ricardo Broz; Rodolfo Gabriel Dondo; Luis Javier Zeballos (Forest Policy and Economics, 2025)

Soil salinity effects on inter-plant signalling in wild cotton are contingent on herbivore load and differentially shape direct and indirect defences - Jonathan Interian-Aguiñaga; Uriel Solís-Rodriguez; Yeyson Briones-May; Patricia Guadarrama-Chávez; Marine Mamin; Mary V. Clancy; Ted C. J. Turlings; Xoaquín Moreira; Luis Abdala-Roberts (Planta, 2025)

A machine learning approach for type 2 diabetes diagnosis and prognosis using tailored heterogeneous feature subsets - J. Ramón Navarro-Cerdán; Pedro Pons-Suñer; Laura Arnal; Joaquim Arlandis; Rafael Llobet; Juan-Carlos Perez-Cortes; Francisco Lara-Hernández; Celeste Moya-Valera; Maria Elena Quiroz-Rodriguez; Gemma Rojo-Martinez; Sergio Valdés; Eduard Montanya; et al. (Medical & Biological Engineering & Computing, 2025)
Type 2 diabetes (T2D) is becoming one of the leading health problems in Western societies, diminishing quality of life and consuming a significant share of healthcare resources. This study presents machine learning models for T2D diagnosis and prognosis, developed using heterogeneous data from a Spanish population dataset (Di@bet.es study). The models were trained exclusively on individuals classified as controls and undiagnosed diabetics, ensuring that the results are not influenced by treatment effects or behavioral changes due to disease awareness. Two data domains are considered: environmental (patient lifestyle questionnaires and measurements) and clinical (biochemical and anthropometric measurements). The preprocessing pipeline consists of four key steps: geospatial data extraction, feature engineering, missing data imputation, and quasi-constancy filtering. Two working scenarios (Environmental and Healthcare) are defined based on the features used, and applied to two targets (diagnosis and prognosis), resulting in four distinct models. The feature subsets that best predict the target have been identified based on permutation importance and sequential backward selection, reducing the number of features and, consequently, the cost of predictions. In the Environmental scenario, models achieved an AUROC of 0.86 for diagnosis and 0.82 for prognosis. The Healthcare scenario performed better, with an AUROC of 0.96 for diagnosis and 0.88 for prognosis. A partial dependence analysis of the most relevant features is also presented. An online demo page showcasing the Environmental and Healthcare T2D prognosis models is available upon request. Graphic abstract

Foliar-Application of Proline Mitigates Salinity Stress in Two Maize (Zea mays L.) Genotypes: A Comparative Study of Growth, Physiology, Chlorophyll Fluorescence, and Ionic Composition - Tayyaba Naz; Muhammad Mazhar Iqbal; Iftikhar Ahmad; Muhammad Adnan Sohail; Shazia Iqbal; Aftab Jamal; Luis Alfonso Rodriguez-Paez; Marcelo F. Pompelli (Journal of Plant Growth Regulation, 2025)

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Observations of Sargassum carbon influx and biogeochemical impact in La Parguera Marine Reserve - Priscilla N. Molina-Cora; Julio M. Morell; Loraine Martell-Bonet; Luis R. Rodriguez-Matos; Julián E. Morell; Maribel Vélez-Rivera (Frontiers in Marine Science, 2025)
The massive influx of pelagic Sargassum spp. species, also known as Sargassum inundation events (SIEs), first arrived at the Caribbean’s coastal waters in 2011. These events have been linked to hypoxia, among other ecological disturbances. Here, we report data from 2022 on (1) an assessment of the relative magnitude of particulate organic carbon (POC) load arising from SIEs into the La Parguera Marine Reserve (LPMR) basin off the southwest coast of Puerto Rico and (2) the biogeochemical impact of SIE in a nearshore mangrove key within the reserve, Monsio Jose Key Bay (MJKB). Our analysis yields that the carbon influx increased by 20% in the LPMR basin and by 103% in MJKB. Weekly observations of Sargassum input, along with the collection and analysis of water samples in MJKB, evidenced a cause-effect relation between Sargassum carbon loading and frequency of hypoxic (DO < 2 mg·L -1 ) and critically acidic conditions (Aragonite saturation, Ω < 2.0). During the 2022 Sargassum season, hypoxic conditions were detected in 43% of samples collected in MJKB. Considering the modulation of biogeochemical parameters by changes in tide height (Δh) and wind speed (m·s -1 ), stepwise multiple regression analyses (RDA-AIC model selection) showed that significant parameters influencing DO, pH, and Ω include the Sargassum carbon influx and Δh ( p < 0.05). These findings strongly support the hypothesis that the additional input of POC influx enhances microbial mineralization rates responsible for depressed oxygen concentrations and acidic conditions, which could be detrimental to coastal ecosystems. This is particularly concerning in areas prone to SIEs where geomorphological features facilitate the entrainment of floating materials. Proper management requires the identification of vulnerable sites and Sargassum removal. Ongoing efforts towards that goal are underway for LPMR.

Subclinical infection and localization of foot-and-mouth disease viral RNA/antigens in apparently healthy Asiatic buffalo under natural condition - Rajeev Ranjan; Jitendra K. Biswal; Nandakumar S. Nair; Karam Pal Singh; Biswajit Das; Jajati Keshari Mohapatra; Saravanan Subramaniam; Manoranjan Rout; Jonathan Arzt; Luis L. Rodriguez; Bramhadev Pattnaik (Veterinary Microbiology, 2025)

Sources, advances, and future prospects of screening food contaminants in plant-based foods by vibrational spectroscopy combined with machine learning - Tong Yu; Siyu Yao; Zhongkun Zhang; Alessandra Fantina Victorio Ramos; Luis Rodriguez-Saona; Jin Wang (Trends in Food Science & Technology, 2025)

Nutritional ketosis modulates the methylation of cancer-related genes in patients with obesity and in breast cancer cells - Paula M Lorenzo; Andrea G Izquierdo; Gemma Rodriguez-Carnero; Nicolas Costa-Fraga; Angel Díaz-Lagares; Cristina Porca; Daniel de Luis; Cristina Tejera; Laura De Paz; Juan Cueva; Diego Bellido; Ana B Crujeiras (Journal of Physiology and Biochemistry, 2025)
Scientific evidence demonstrates that a very low-calorie ketogenic diet (VLCKD) is effective and beneficial in the treatment of obesity, capable of reversing the methylome associated with obesity and has immunomodulatory capacity. This effect is in part promoted by nutritional ketosis and could be involved in counteracting obesity-related cancer. The aim of this study was to evaluate the effect of nutritional ketosis on the methylation of genes related to tumor processes in patients with obesity and in breast cancer cells. Based on methylome data (Infinium MethylationEPIC BeadChip, Illumina) from patients with obesity treated with a VLCKD for weight loss ( n = 10; n = 5 women, age = 48.8 ± 9.20 years, BMI = 32.9 ± 1.4 kg/m2), genes belonging to cancer-related pathways were specifically evaluated and further validated in vitro in MDA-MB-231 (triple negative) and MCF7 (RE positive) breast tumor cells pretreated for 72 h with βOHB, the main ketone body, secretome from visceral (VATs) or subcutaneous (SATs) adipose tissue of patients with obesity. The cell tumoral phenotype was evaluated by proliferation assay and expression of cancer-related genes. VLCKD-induced nutritional ketosis promoted changes in the methylation of 18 genes (20 CpGs; 17 hypomethylated, 3 hypermethylated) belonged to cancer-related pathways with MAPK10, CCN1, CTNNA2, LAMC3 and GLI2 being the most representative genes. A similar pattern was observed in the MDA-MB-231 cells treated with β-OHB, without changes in MCF7. These epigenetic changes paralleled the tumoral phenotype modulated by the treatments. Taking together these results highlight the potential role of VLCKD as an adjuvant to anticancer treatment in groups more susceptible to the development of cancer such as patients with obesity, exerting epigenetic regulation through nutritional ketosis and weight loss.

Mush system heterogeneities control magma composition and eruptive style on the Ocean Island of El Hierro, Canary Islands - Claudia Prieto-Torrell; Helena Albert; Meritxell Aulinas; Eloi González-Esvertit; Ilenia Arienzo; Guillem Gisbert; Valentin R. Troll; Jose-Luis Fernandez-Turiel; Alejandro Rodriguez-Gonzalez; Francisco-Jose Perez-Torrado (Contributions to Mineralogy and Petrology, 2025)
The study of recent eruptions in Ocean Islands (OIs) provides a unique window into the magma dynamics governing their plumbing systems and the mechanisms leading to eruptions. Here we present an integrated approach to unravel the dynamics of magmatic plumbing systems through detailed spatial, petrological, and geochemical characterisation of volcanic products ranging from crystal-rich ankaramitic lavas to trachytic tephras. We focus on the textural and geochemical spatial variations of 42 Holocene subaerial eruptions at the OI of El Hierro (Canary Islands), as well as on their petrogenetic significance for magmatic evolution and plumbing system architecture. Integrating geochemical data within fractional crystallisation modelling and mass balance calculations reveals that ankaramitic and porphyritic lavas with phenocryst modal abundances > 10 vol% result from melt extraction and crystal accumulation. Aphyric to sub-aphyric eruption products and porphyritic lavas with phenocryst modal abundances < 10 vol% usually follow fractional crystallisation trajectories that start at ~ 10 wt% MgO. Periodic extraction of evolved melt from crystal mushes likely led to the occurrence of minor trachytic eruptions, which are difficult to reconcile with simple closed system fractional crystallisation trends. A complex, heterogeneous crustal mush system beneath El Hierro is, in fact, the most reliable scenario to explain the wide range of textures, whole-rock and mineral compositions, and the overall surface distribution of vents and eruptive styles displayed by the Holocene volcanism on the island. Our integrated findings highlight the importance of a combined field, petrological, and geochemical study to decipher plumbing system dynamics of OI magmatism. The results allow us to put forward an updated conceptual model of the current plumbing architecture of El Hierro’s volcanic system during the Holocene.

Earth's most needed uncultivated aquatic prokaryotes - Sophie A. Simon; Vera Aschmann; Annika Behrendt; Michael Hügler; Lisa M. Engl; Marion Pohlner; Sönke Rolfes; Thorsten Brinkhoff; Bert Engelen; Martin Könneke; Luis M. Rodriguez-R; Till L.V. Bornemann; et al. (Water Research, 2025)

Zoonotic Parasites in Hoplosternum littorale Acquired in the Market of Santa Clara, in the City of Iquitos, Loreto-Peru - Germán Augusto Murrieta Morey; Stephanie Geovana Reyes Llanos; Luciano Alfredo Rodriguez Chu; Avita Celeste Taricuarima Dreyfus; Luis Armando García Solsol; Roger Fernando Chuquipiondo Sánchez; Ehrlich Yam Llasaca Calizaya (Acta Parasitologica, 2025)

Characterization and Differential Expression of Sex Genes in Adults of Tropical Gar (Atractosteus tropicus) - Otilio Méndez-Marin; María de Lourdes Jiménez-Badillo; Carina Shianya Álvarez-Villagomez; Talhia Martínez-Burguete; Uriel Rodriguez-Estrada; Gloria Gertrudys Asencio-Alcudia; Graciela María Pérez-Jiménez; Gabriela Galindo-Cortés; Virgilio Eugenio Arenas-Fuentes; Rafael Martínez-García; Luis Daniel Jiménez-Martínez; Carlos Alfonso Alvarez-González (Fishes, 2025)
The tropical gar (Atractosteus tropicus) is a primitive freshwater fish of significant commercial importance in southeastern Mexico. However, its population is in danger due to habitat loss and overexploitation. Cultivation emerges as a viable reproductive management strategy; yet further studies are crucial to understanding molecular markers guiding reproductive management, differentiation, and sexual maturation in this species. We analyzed the expression of five sex-related genes (foxl2, sox9, cyp17a1, dmrt1, and cyp19a1) in the brain, liver, and gonads of adult A. tropicus (four females and five males). Methodologically, we collected samples and conducted RNA extraction, cDNA synthesis, and gene expression analysis using qPCR. The gonadal histology provided morphological context that reveals that the differential expression of genes establishes differences between sexes. The sexual phenotype of females is observed with the high expression of dmrt1, while in males, there is a reduction in the expression of dmrt1 and high levels of sox9, foxl2, and cyp17a1. Our findings establish dmrt1 and cyp19a1 as potential sex biomarkers and provide a molecular basis for developing sexing protocols in A. tropicus.

Advancing Patient Advocacy in Mycology: Cultivating Collaboration in Education, Research, and Policy - Rob Purdie; Rasha Kuran; Ana Alastruey-Izquierdo; Hatim Sati; Juan Luis Rodriguez-Tudela; Martin Hoenigl; John Perfect; Rita Oladele; Thomas J. Walsh; Tom Chiller (Mycopathologia, 2025)
In the healthcare landscape, diseases such as cancer and HIV/AIDS have benefited from the patient's perspective. For fungal diseases, the patient voice remains absent in critical areas such as policy formulation, funding decisions, and research priorities. Patients affected by fungal disease, along with their caregivers and advocacy groups, possess invaluable insights into the challenges and unmet needs they face. By elevating their voices and experiences, policymakers, funding agencies, and researchers can gain a more comprehensive understanding of the multifaceted nature of fungal disease and the urgency of addressing them. This paper addresses the pressing need for a coordinated effort to elevate the patient voice in advocating for improved policies, increased funding, and enhanced research initiatives regarding fungal disease.

Analysis of high-molecular-weight proteins using MALDI-TOF MS and machine learning for the differentiation of clinically relevant Clostridioides difficile ribotypes - Ana Candela; David Rodriguez-Temporal; Mario Blázquez-Sánchez; Manuel J. Arroyo; Mercedes Marín; Luis Alcalá; Germán Bou; Belén Rodríguez-Sánchez; Marina Oviaño (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Atlantic arc Lander Monitoring (ALaMo): An Emerging Network of Low-Cost Lander Arrays for Ocean Bottom Observations - Cesar González-Pola; Caroline Cusack; Ignacio Urquijo; Rocio Graña; Luis Rodriguez-Cobo; Ricardo Sánchez-Leal; Glenn Nolan; Miguel Piecho-Santos (Oceanography, 2025)
The need to establish a sustained Global Ocean Observing System (GOOS) has long been recognized by the international ocean science community. Established in 1991 and led by the Intergovernmental Oceanographic Commission of the United Nations Educational, Scientific, and Cultural Organization (IOC-UNESCO), GOOS develops guidelines and coordinates regional alliances across the world’s ocean basins to evolve the system. The need to sustainably expand GOOS has recently gained urgency as expressed in the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) Challenge 7: Ensure a sustainable ocean observing system across all ocean basins that delivers accessible, timely, and actionable data and information to all users.

Occurrence, characterization, and ecological risk analysis of petroleum hydrocarbons in water and sediments following large-scale field simulated oil spills at the experimental lakes area, Northwestern Ontario, Canada - Zeyu Yang; Keval Shah; Bruce Hollebone; Sonia Laforest; Madison MacGillivray; Diane Dey; Jose Luis Rodriguez; Benoit Lalonde; Chun Yang; Vanessa Beaulac; Jules M. Blais; Mark Hanson; et al. (Marine Pollution Bulletin, 2024)

Effect of aging time on the physicochemical properties of lime used to preserve corn postharvest - Efren Herrera-López; Sylvanus Odjo; Luis F. Zubieta-Otero; Brenda L. Contreras-Jiménez; Fabiola Curiel-Ayala; Lina Garcia-Mier; Mario E. Rodriguez-Garcia (Journal of Stored Products Research, 2024)

Options and considerations for validation of prokaryotic names under the SeqCode - Stephanus N. Venter; Luis M. Rodriguez-R; Maria Chuvochina; Marike Palmer; Philip Hugenholtz; Emma T. Steenkamp (Systematic and Applied Microbiology, 2024)

Extraction of bio-hydroxyapatite from devilfish (Loricariidae) for the fluoride and cadmium adsorption from water and its feasible photocatalytic properties - Hilda G. Cisneros-Ontiveros; Luis F. Zubieta-Otero; Nahum A. Medellín-Castillo; Alfredo I. Flores-Rojas; Mario E. Rodriguez-Garcia (Chemosphere, 2024)

Dynamic response of a pipe with geometrical restriction subjected to gas-liquid internal flow - Luis F.A. Alegría; L. Enrique Ortiz-Vidal; Johann E.C. Bolivar; C.E. Álvarez-Pacheco; Leopoldo P.R. de Oliveira; Oscar M.H. Rodriguez (Ocean Engineering, 2024)

Physicochemical changes in Amaranthus spp grains, flour, isolated starch, and nanocrystals during germination and malting - Elsa Gutiérrez-Cortez; Ezequiel Hernandez-Becerra; Luis Fernando Zubieta-Otero; Marcela Gaytán-Martínez; Oscar Yael Barrón-García; Mario Enrique Rodriguez-Garcia (Food Chemistry, 2024)

Fabrication, characterization, and potential applications of re-assembled casein micelles - Muhammed Aslam Khan; Yacine Hemar; Jiecheng Li; Zhi Yang; Luis M. De Leon-Rodriguez (Critical Reviews in Food Science and Nutrition, 2024)

“Hg distribution and accumulation in soil and vegetation in areas impacted by artisanal gold mining in the Southern Amazonian region of Madre de Dios, Peru.” - Maria J. Rodriguez-Pascual; Claudia M. Vega; Natasha Andrade; Luis E. Fernández; Miles R. Silman; Alba Torrents (Chemosphere, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Pharmacokinetics and safety of LEAD-452, an EGFR-specific 4-1BB-agonistic trimerbody in non-human primates - Rocío Navarro; Susana Frago; Oana Hangiu; Ainhoa Erce-Llamazares; Rodrigo Lázaro-Gorines; Miguel A. Morcillo; José L. Rodriguez-Peralto; Laura Sanz; Marta Compte; Luis Alvarez-Vallina (Toxicology and Applied Pharmacology, 2024)

Predicting milk-derived hydrogel-forming peptides with TANGO - Muhammed Aslam Khan; Yacine Hemar; Ka-Wing Cheng; Florian J. Stadler; Luis M. De Leon-Rodriguez (International Dairy Journal, 2024)

Evaluation of the physical and mechanical properties of concrete with the incorporation of recycled concrete aggregate - Sócrates Pedro Muñoz Pérez; Jarlin Miguel Pardo Becerra; Juan Martín García Chumacero; Elver Sánchez Diaz; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodriguez Laffite; José Luis Quispe Osorio; Yander Mavila Briceño Mendoza (Innovative Infrastructure Solutions, 2024)

Quis custodiet ipsos custodes? A call for community participation in the governance of the SeqCode - Iain C. Sutcliffe; Luis M. Rodriguez-R; Stephanus N. Venter; William B. Whitman (Systematic and Applied Microbiology, 2024)

Insecticidal action, repellency, and toxicity mechanism of the essential oil of Lippia turbinata against the stored product pest Rhipibruchus picturatus (F.) - Valeria Tapia Mattar; José Luis Borioni; Axel Hollman; Sergio A. Rodriguez (Pesticide Biochemistry and Physiology, 2024)

Closing the energy flexibility gap: Enriching flexibility performance rating of buildings with monitored data - Manuel de-Borja-Torrejon; Gerard Mor; Jordi Cipriano; Angel-Luis Leon-Rodriguez; Thomas Auer; Jenny Crawley (Energy and Buildings, 2024)

Graphene-based Semiconductors for Photocatalytic Degradation of Organic Dye from Wastewater: A Comprehensive Review - Pierre G. Ramos; Harry Rivera; Luis A. Sánchez; María E. Quintana; Juan M. Rodriguez (Water, Air, & Soil Pollution, 2024)

Short-term associations between fine particulate air pollution and cardiovascular and respiratory mortality in 337 cities in Latin America - Nelson Gouveia; Jordan L. Rodriguez-Hernandez; Josiah L. Kephart; Ana Ortigoza; Ricardo Morales Betancourt; Jose Luis Texcalac Sangrador; Daniel A. Rodriguez; Ana V. Diez Roux; Brisa Sanchez; Goro Yamada (Science of The Total Environment, 2024)

Glass fiber reinforced concrete: overview of mechanical and microstructural analysis - Sócrates Pedro Muñoz Pérez; Juan Fernando Santisteban Purizaca; Sandrita Maribel Castillo Matute; Juan Martín García Chumacero; Elver Sánchez Diaz; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodriguez Laffite; José Luis Quispe Osorio; Yander Mavila Briceño Mendoza (Innovative Infrastructure Solutions, 2024)

Spatio-temporal trends of mercury levels in alluvial gold mining spoils areas monitored between rainy and dry seasons in the Peruvian Amazon - Edwin Becerra-Lira; Liset Rodriguez-Achata; Adenka Muñoz Ushñahua; Ronald Corvera Gomringer; Evert Thomas; Jorge Garate-Quispe; Litcely Hilares Vargas; Pedro Romel Nascimento Herbay; Luis Alfredo Gamarra Miranda; Eleuterio Umpiérrez; Juan Antonio Guerrero Barrantes; Martin Pillaca; et al. (Environmental Research, 2024)

Controlled Elicitation and Greenhouse Acclimation Time Effects on Morphological and Biochemical Variables in Collections of Heliopsis longipes from Central México - Ixchel Parola-Contreras; Luis Felipe Guzman-Rodriguez; Erik Gustavo Tovar-Perez; Brenda Zulema Guerrero-Aguilar; Blanca Amalia Amaro-Gonzalez; Alejandra Rojas-Molina; Irineo Torres-Pacheco; Jose Luis Pons-Hernandez; Mario Martin Gonzalez-Chavira; Ramon Gerardo Guevara-Gonzalez (Journal of Plant Growth Regulation, 2024)

Human health and environmental risk assessment of metals in community gardens of Winnipeg, Manitoba, Canada - Teresa Senderewich; Doug Goltz; Jose Luis Rodriguez-Gil; Brian Laird; Ryan S. Prosser; Mark L. Hanson (Environmental Science and Pollution Research, 2024)

Conjugation of lesser mealworm (Alphitobius diaperinus) larvae protein with polyphenols for the development of innovative antioxidant emulsifiers - Aurélie Ballon; Maria-Paz Romero; Luis E. Rodriguez-Saona; Sílvia de Lamo-Castellví; Carme Güell; Montserrat Ferrando (Food Chemistry, 2024)

Andean soil-derived lignocellulolytic bacterial consortium as a source of novel taxa and putative plastic-active enzymes - Laura Díaz-García; Maria Chuvochina; Golo Feuerriegel; Boyke Bunk; Cathrin Spröer; Wolfgang R. Streit; Luis M. Rodriguez-R; Jörg Overmann; Diego Javier Jiménez (Systematic and Applied Microbiology, 2024)

Investigating the gastrointestinal physiology of mature horses with and without a history of cribbing behavior in response to feeding a digestive support supplement - Ana M. Arias-Esquivel; Ana C. Cerqueira de Melo Vasco; Jill Lance; Lori K Warren; Luis A Rodriguez-Campos; Megan C. Lee; Christina N. Rodriguez; Carissa L Wickens (Journal of Equine Veterinary Science, 2024)

A user's guide to the bioinformatic analysis of shotgun metagenomic sequence data for bacterial pathogen detection - Blake G. Lindner; Kenji Gerhardt; Dorian J. Feistel; Luis M. Rodriguez-R; Janet K. Hatt; Konstantinos T. Konstantinidis (International Journal of Food Microbiology, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Are mangroves hotspots of marine litter for surrounding beaches? Hydrodynamic modeling and quali-quantitative analyses of waste in southeastern Brazil - Luis Felipe de Almeida Duarte; Renan Braga Ribeiro; Tierry Val de Medeiros; William Rodriguez Scheppis; Giovana Teixeira Gimiliani (Regional Studies in Marine Science, 2023)

Corrigendum to “JM-20 treatment prevents neuronal damage and memory impairment induced by aluminum chloride in rats” [Neurotoxicology 87 (2021) 70–85] - Maylin Wong-Guerra; Yanay Montano-Peguero; Jeney Ramírez-Sánchez; Javier Jiménez-Martin; Luis Arturo Fonseca-Fonseca; Daniela Hernández-Enseñat; Yasmine Nonose; Odalys Valdés; Abel Mondelo-Rodriguez; Yaquelin Ortiz-Miranda; Gretchen Bergado; Tania Carmenate; et al. (NeuroToxicology, 2023)

Modulation of the lipolysis and subsequent antibacterial activity of the fat from black soldier fly (Hermetia illucens) by the combined selection of slaughtering, drying and defatting methods of the larvae - Raúl Hurtado-Ribeira; Jose Manuel Silvan; Tiziana Fornari; Luis Vázquez; Adolfo J. Martinez-Rodriguez; Diana Martin (Innovative Food Science & Emerging Technologies, 2023)

Considerations on the action of polyphenoloxidase on 4-hydroxy-cinnamic acid. Molecular docking simulation - Pablo García Molina; Jose Antonio Teruel Puche; Jose Luis Muñoz Muñoz; Jose Neptuno Rodriguez Lopez; Francisco García Canovas; Francisco García Molina (Food Chemistry, 2023)

Board of directors and environmental practices: the effect of board experience, culture, and tenure - Isabel Gallego-Álvarez; Luis Rodriguez-Dominguez (Environment, Development and Sustainability, 2023)
This study analyses whether board diversity in terms of gender and culture, as well as members’ experience and tenure, has a positive influence on the undertaking of environmental practices. The analysis was performed on a broad sample of international companies from 29 countries, on the basis of an index made up of 55 environmental activities. We designed a Tobit model in which the index of environmental practices is a function of several features of the board. The findings confirm that more diverse boards, with more experienced and long-tenured members, are more prone to the environmental commitment by promoting a broader range of environmental initiatives. The article provides new insights in terms of the influence of board diversity in culture, experience, and tenure. We extend previous literature by analysing these factors, whose effects have been less studied, rather than other drivers (such as board size and independence). Corporate governance mechanisms, and more specifically, the board of directors, may play an essential role in ensuring congruence among a firm’s actions, stakeholders’ demands, and societal expectations. The advantages derived from a wider knowledge base and diversity in the board lead to a pro-environmental vision on behalf of the company.

Long-term exposure to ambient fine particulate matter and carotid intima media thickness at bilateral, left and right in adults from Mexico City: Results from GEA study - Rocio Torrico- Lavayen; Gilberto Vargas-Alarcón; Horacio Riojas-Rodriguez; Marco Sánchez-Guerra; José Luis Texcalac-Sangrador; Eduardo Ortiz-Panozo; Iván Gutiérrez-Avila; Andrea De Vizcaya-Ruiz; Andres Cardenas; Rosalinda Posadas-Sánchez; Citlalli Osorio-Yáñez (Chemosphere, 2023)

Wood decay fungi and their bacterial interaction partners in the built environment – A systematic review on fungal bacteria interactions in dead wood and timber - Julia Embacher; Susanne Zeilinger; Martin Kirchmair; Luis M. Rodriguez-R; Sigrid Neuhauser (Fungal Biology Reviews, 2023)

Ambient temperature modulates body weight changes in patients with advanced oncological diseases and anorexia cachexia syndrome - Paloma Encinas; Jose Luis Rodriguez-Arias; Luis Miguel Luengo Pérez; Daniel Cortizo; Emilio Gutierrez (International Journal of Biometeorology, 2023)
Objective To assess the impact of ambient temperature (AT) on the evolution of bodyweight in patients with heterogeneous types of cancer in advanced stages of the disease (stages III and IV) and anorexia- cachexia syndrome (ACS). Methods A prospective naturalistic multicenter study of patients undergoing oncological treatment at four hospitals during a three-year period (2017–2020) in the Autonomous Community of Extremadura in southwestern Spain with a continentalized Mediterranean climate of mild and relatively rainy winters, and particularly hot and sunny summers. Bodyweight changes were obtained from the medical records of 84 oncological patients (59 men and 25 women, age range 37–91 yrs). Mean monthly AT was used to examine the association of weight changes across cold and warm bimesters -BIMs (December and January, vs. July and August), Trimesters -TRIMs (July to September vs. December to February), and Semesters -SEMs (May to October vs. November to April). Weight changes between two consecutive weight measures were categorized as weight gain, weight loss, or no weight change. Differences across cold and warm seasons were analysed using parametric (ANOVA), and nonparametric statistics (Chi-square and binomial z tests). An alpha-rate of 0.05 was used for all analyses. Results A weight loss trend was observed during BIMs cold periods in comparison to warm ones ( p 0.04). However, differences in average bodyweight were not significant. The negative impact of cold periods was more marked in men than in women, ( p = 0.05; p = 0.03, for cold vs. warm BIMs and TRIMs, respectively). In contrast, significantly higher weight gain percentages were found in women during warm TRIMs and SEMs ( p = 0.03, and p = 0.01, respectively). As for the number of patients dying during the study ( N = 56; 39 men, 17 women), there were a significant interaction between temperature (cold/warm), and mean weight F ( 1, 499) = 6.06, p = 0.01, which revealed a pattern of weight loss in the cold semester as opposed to weight gain during the warm SEM months. Conclusions AT temperature modulated body weight changes in patients with advanced oncological disease and ACS. Two main limitations of the study were the absence of information on diets as a moderating factor of weight loss/gain, and the lack of the patients’ weight measurements closest to the date of diagnosis prior to admittance to the study. As for the practical implications, it remains to be seen whether an adjunctive heat supply will serve a buffering effect on weight loss during colder seasons for patients with advanced cancer and ACS.

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

LIPRNAseq: a method to discover lipid interacting RNAs by sequencing - Andrea Bayona-Hernandez; Susana Guerra; Irma Angélica Jiménez-Ramirez; Martin Sztacho; Pavel Hozak; Luis Carlos Rodriguez-Zapata; Alejandro Pereira-Santana; Enrique Castaño (Molecular Biology Reports, 2023)

Influence of rice husk ash (RHA) with gypsum and ichu fibers in the processing of geopolymers - Sócrates Pedro Muñoz Pérez; Samuel Charca Mamani; Luigui Italo Villena Zapata; Jorge Luis Leiva Piedra; Simon Gonzales Ayasta; Ernesto Dante Rodriguez Lafitte; Fidel Gregorio Aparicio Roque; Omar Coronado Zuloeta (Innovative Infrastructure Solutions, 2023)

Metals and metalloids in high-altitude Pyrenean lakes: sources and distribution in pre-industrial and modern sediments - Azibar Rodriguez-Iruretagoiena; Ainara Gredilla; Silvia Fdez-Ortiz de Vallejuelo; Gorka Arana; Maite Meaurio; Juan Manuel Madariaga; Jean Christophe Auguet; Aridane González González; Oleg S. Pokrovsky; Luis Camarero; Alberto de Diego (Environmental Science and Pollution Research, 2023)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Endometrial inflammatory response to insemination in jennies - Angeles Rodriguez; Myriam Boeta; Luis Zarco (Journal of Equine Veterinary Science, 2023)

Influence of secretome obtained from preovulatory follicular fluid on energy metabolism and meiotic competence of equine cumulus–oocyte complexes - Jose M Ortiz-Rodriguez; Pablo Fernández-Hernández; Marcos Luis-Calero; Marcella Spinaci; Diego Bucci; Beatriz Macías-García; Lauro González-Fernández (Journal of Equine Veterinary Science, 2023)

Effect of transvaginal oocyte aspiration on progesterone concentrations and estrous cycle length in domestic jennies - Ana Flores Bragulat; Carolina Alonso; Catalina Castañeira; Ayelen Rodriguez; Jose M Zeledon; Luis Losinno; Andres Gambini (Journal of Equine Veterinary Science, 2023)

Functional seed traits as predictors of germination and seedling growth for species with potential for restoration in Caquetá, Colombia - María N. Nieto Guzmán; Luis C. Beltrán; Carlos H. Rodriguez; Lilia L. Roa-Fuentes (Trees, 2023)
Key message Pre-germination requirements are not accurately predicted by seed traits of size and mass. However, small-seeded species show high germination and slow early seedling growth rates. Abstract Deforestation in the tropics is one of the greatest biodiversity crises of the Anthropocene. In response, tropical countries such as Colombia have committed to restoring degraded lands and reconnecting forest fragments. To contribute to this mission, we evaluated how easy-to-measure seed functional traits predicted germination requirements and early seedling growth rates (RGRs) for 11 tree species native to the Andean-Amazon piedmont region. Pre-sowing treatments followed a 3 × 3 factorial design: three light conditions (full, partial, and no light) and three pre-germination treatments (hot water, abrasion, and control). A cluster analysis grouped species into three groups driven chiefly by highly correlated variables of seed size and mass. However, species within and among functional groups differed in their response to pre-germination treatments. One exception includes the small-seeded species group responding with little-to-no germination to the absence of light. Since functional traits were highly correlated, we used Principal Component Regression (PCR) to predict germination metrics (germination percentage, velocity, and vigor) and RGRs. The multivariate trait axis of seed size and seed mass measurements (PC1) correlated negatively with germination metrics and positively with RGRs. Our results highlight the challenges associated with using easy-to-measure functional traits to deduce the most effective pre-sowing treatment. Other more relevant functional traits can be measured in lab, but a shotgun approach to testing pre-germination treatments may be more cost-effective. High germination in small-sized seed species highlights the early-successional niche these species occupy, but reduced RGR may represent a tradeoff associated with having relatively few resources stored in seed.

Unrecognized species diversity and endemism in the cichlid genus Bujurquina (Teleostei: Cichlidae) together with a molecular phylogeny document large-scale transformation of the western Amazonian river network and reveal complex paleogeography of the Ecuadorian Amazon - Oldřich Říčan; Štěpánka Říčanová; Luis Roger Rodriguez Haro; Cecilia Elizabeth Rodriguez Haro (Hydrobiologia, 2023)

A novel and stretchable carbon-nanotube/Ni@TiO2:W photocatalytic composite for the complete removal of diclofenac drug from the drinking water - Ernesto Valadez-Renteria; Rafael Perez-Gonzalez; Christian Gomez-Solis; Luis Armando Diaz-Torres; Armando Encinas; Jorge Oliva; Vicente Rodriguez-Gonzalez (Journal of Environmental Sciences, 2023)

Corrigendum to “Forest Hydrology in Chile; paste, present, and future” [J. Hydrol. 616 (2023)] - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barria; et al. (Journal of Hydrology, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Forest hydrology in Chile: Past, present, and future - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barría; et al. (Journal of Hydrology, 2023)

Evaluation of inhibitory effects of some novel phenolic derivatives on the mushroom tyrosinase activity - Pablo García Molina; Jose Luis Muñoz Muñoz; Jose Antonio Teruel Puche; Jose Neptuno Rodriguez Lopez; Francisco Garcia Canovas; Francisco Garcia Molina (Food Chemistry, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Mechanistic insight into the synthesis of fucooligosaccharides by α-L-fucosidase from Thermotoga maritima belonging to the GH29 family: in silico study - Mauricio E. Pavón-Chimal; Carlos Jiménez-Pérez; Francisco Guzmán-Rodriguez; Sergio Alatorre-Santamaría; Luis G. González-Olivares; Mariano García-Garibay; Lorena Gómez-Ruiz; Gabriela Rodríguez-Serrano; Alma E. Cruz-Guerrero (Biologia, 2022)

Comprehensive Certification of the Furvina Production by Modeling Quality Control Parameters - Zenia Perez-Rodriguez; Orlando Alvarez; Zenaida Rodríguez-Negrin; Amalia Maria Calvo; Hector Luis Valdés-Negrín; Michael Pérez-Rodríguez (Journal of Pharmaceutical Innovation, 2022)

Diagnosis of bacterial meningitis caused by Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae using a multiplex real-time PCR technique - María Noemí Carnalla-Barajas; Araceli Soto-Noguerón; Lucila Martínez-Medina; Maria Elizabeth Olvera-Herrera; Juan Luis Mosqueda-Gómez; Patricia Rodríguez-Cortez; Rayo Morfin-Otero; Eduardo Rodriguez-Noriega; Antonio Luévanos-Velázquez; Mariana Merlo-Palomera; Sergio Esparza-Ahumada; Francisco Márquez-Díaz; et al. (Brazilian Journal of Microbiology, 2022)

Correction to: Multiple Alr genes exhibit allorecognition-associated variation in the colonial cnidarian Hydractinia - Henry Rodriguez-Valbuena; Andrea Gonzalez-Muñoz; Luis F. Cadavid (Immunogenetics, 2022)

Multiple Alr genes exhibit allorecognition-associated variation in the colonial cnidarian Hydractinia - Henry Rodriguez-Valbuena; Andrea Gonzalez-Muñoz; Luis F. Cadavid (Immunogenetics, 2022)

A novel equation that incorporates the linear and hyperbolic nature of the force–velocity relationship in lower and upper limb exercises - Julian Alcazar; Fernando Pareja-Blanco; Carlos Rodriguez-Lopez; Hector Gutierrez-Reguero; Juan Sanchez-Valdepeñas; Pedro J. Cornejo-Daza; Ignacio Ara; Luis M. Alegre (European Journal of Applied Physiology, 2022)

In vivo subchronic effects of ciguatoxin-related compounds, reevaluation of their toxicity - Sandra Raposo-García; Andrea Boente-Juncal; Mercedes Rodriguez-Vieytes; Mercedes Camiña; Celia Costas; Alejandro Cao; M. Carmen Louzao; Manuel Cifuentes; Carmen Vale; Luis M. Botana (Archives of Toxicology, 2022)
Ciguatoxins are marine compounds that share a ladder-shaped polyether structure produced by dinoflagellates of the genus Gambierdiscus and Fukuyoa , and include maitotoxins (MTX1 and MTX3), ciguatoxins (CTX3C) and analogues (gambierone), components of one of the most frequent human foodborne illness diseases known as ciguatera fish poisoning. This disease was previously found primarily in tropical and subtropical areas but nowadays, the dinoflagellates producers of ciguatoxins had spread to European coasts. One decade ago, the European Food Safety Authority has raised the need to complete the toxicological available data for the ciguatoxin group of compounds. Thus, in this work, the in vivo effects of ciguatoxin-related compounds have been investigated using internationally adopted guidelines for the testing of chemicals. Intraperitoneal acute toxicity was tested for maitotoxin 1 at doses between 200 and 3200 ng/kg and the acute oral toxicity of Pacific Ciguatoxin CTX3C at 330 and 1050 ng/kg and maitotoxin 1 at 800 ng/kg were also evaluated showing not effects on mice survival after a 96 h observation period. Therefore, for the following experiments the oral subchronic doses were between 172 and 1760 ng/kg for gambierone, 10 and 102 ng/kg for Pacific Ciguatoxin CTX3C, 550 and 1760 ng/kg for maitotoxin 3 and 800, 2560 and 5000 ng/kg for maitotoxin 1. The results presented here raise the need to reevaluate the in vivo activity of these agents. Although the intraperitoneal lethal dose of maitotoxin 1 is assumed to be 50 ng/kg, without chemical purity identifications and description of the bioassay procedures, in this work, an intraperitoneal lethal dose of 1107 ng/kg was obtained. Therefore, the data presented here highlight the need to use a common procedure and certified reference material to clearly establish the levels of these environmental contaminants in food.

Regulatory mechanisms behind the phenotypic plasticity associated with Setaria italica water deficit tolerance - Vanessa Fuentes Suguiyama; Jae Diana Paredes Rodriguez; Tatiane Cristina Nicomedio dos Santos; Bruno Silvestre Lira; Luis Alejandro de Haro; João Paulo Naldi Silva; Eduardo Leite Borba; Eduardo Purgatto; Emerson Alves da Silva; Nicolas Bellora; Fernando Carrari; Danilo da Cruz Centeno; et al. (Plant Molecular Biology, 2022)

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Trends in the use of oral anticoagulants, antiplatelets and statins in four European countries: a population-based study - Luis A. García Rodríguez; Lucía Cea Soriano; Francisco J. de Abajo; Francesca Valent; Jesper Hallas; Miguel Gil; Chiara Cattaruzzi; Sara Rodriguez-Martin; Pareen Vora; Montse Soriano-Gabarró; David Gaist (European Journal of Clinical Pharmacology, 2022)
Purpose To evaluate time trends in the prevalence of antithrombotic and statin use in four European countries. Methods Using population-based data from the United Kingdom, Denmark, Spain and Italy between 2010 and 2018, we calculated standardized annual prevalence proportions of antithrombotics and statin use, and changes in prevalence proportions (2018 vs. 2010). Results Prevalence proportion of statins increased from 24.8% to 24.6% (UK), 21.0% to 22.3% (Region of Southern Denmark [RSD]), 12.9% to 14.3% (Udine, Italy), and 20.3% to 23.2% (Spain). Prevalence proportions of antithrombotics declined in all four countries: 18.7% to 15.9% (UK; − 2.8% points), 18.9% to 18.1% (RSD; − 0.8% points), 17.7% to 16.6% (Udine; − 1.1% points) and 15.0% to 13.6% (Spain; − 1.4% points). These declines were driven by reductions in low-dose aspirin use: 15.3% to 8.9% (UK; − 6.4% points), 16.3% to 9.5% (RSD; − 6.8% points), 13.5% to 11.6% (Udine; − 1.9% points), and 10.2% to 8.8% (Spain; − 1.4% points). In the UK, low-dose aspirin use declined from 9.1% to 4.3% (− 4.8% points) for primary CVD prevention, and from 49.6% to 36.9% (− 12.7% points) for secondary prevention. Oral anticoagulant use gradually increased but did not fully account for the decrease in low-dose aspirin use. Conclusions Antithrombotic use in the UK, RSD, Udine and Spain declined between 2010 and 2018, driven by a reduction in use of low-dose aspirin that is not completely explained by a gradual increase in OAC use. Use of statins remained constant in the UK, and increased gradually in the RSD, Udine and Spain.

Definition of an Artificial Reef Unit through Hydrodynamic and Structural (CFD and FEM) Models—Application to the Ares-Betanzos Estuary - María Isabel Lamas Galdo; María Jesús Rodríguez Guerreiro; Javier Lamas Vigo; Ismael Ameneiros Rodriguez; Ricardo Veira Lorenzo; Juan Carlos Carral Couce; Luis Carral Couce (Journal of Marine Science and Engineering, 2022)
The application of hydrodynamics to the definition of artificial reefs is of great interest since the positioning of the artificial reef modules on the sea floor alters the water velocity field, causing an appropriate circulation of nutrients and promoting a habitat for settling desired species. Nevertheless, the designs must be subjected to a structural calculation that will condition the constructive process to be applied. The present research proposes a methodology to determine the geometry of an artificial reef in terms of hydrodynamic and structural criteria. The solution proposed was analyzed through Computational Fluid Dynamics (CFD) and the Finite Element Method (FEM). Using concrete as base material for artificial reefs, four different dosages were proposed with different proportions of cement and water, leading to different mechanical properties, which determine different constructive strategies, such as dwell time in the mold. From the hydrodynamic point of view, it was found that the solution proposed provides a proper replacement of nutrients. From the structural point of view, it was found that the solution proposed does not need steel reinforcements in concrete, which improves the sustainability of the artificial reef. The four different concrete dosages will condition the constructive strategy through the dwelling time in the mold and, for any established production, the necessary number of molds (formworks).

Cryptic speciation in Orbilia xanthostigma and O. leucostigma (Orbiliomycetes): an aggregate with worldwide distribution - Hans-Otto Baral; Peter Johnston; Luis Quijada; Rosanne Healy; Donald H. Pfister; Katherine F. LoBuglio; Valentina Rodriguez; Evi Weber (Mycological Progress, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Use of pooled serum samples to assess herd disease status using commercially available ELISAs - Juan Heberth Hernandez-Medrano; Luis Fernando Espinosa-Castillo; Ana D. Rodriguez; Carlos G. Gutierrez; Wendela Wapenaar (Tropical Animal Health and Production, 2021)
Pooled samples are used in veterinary and human medicine as a cost-effective approach to monitor disease prevalence. Nonetheless, there is limited information on the effect of pooling on test performance, and research is required to determine the appropriate number of samples which can be pooled. Therefore, this study aimed to evaluate the use of pooled serum samples as a herd-level surveillance tool for infectious production-limiting diseases: bovine viral diarrhoea (BVD), infectious bovine rhinotracheitis (IBR), enzootic bovine leukosis (EBL) and Neospora caninum (NC), by investigating the maximum number of samples one can pool to identify one positive animal, using commercial antibody-detection ELISAs. Four positive field standards (PFS), one for each disease, were prepared by pooling highly positive herd-level samples diagnosed using commercially available ELISA tests. These PFS were used to simulate 18 pooled samples ranging from undiluted PFS to a dilution representing 1 positive in 1,000 animals using phosphate-buffered saline as diluent. A 1:10 dilution of the PFS resulted in positive results for IBR, BVD and EBL. Moreover, for IBR and BVD, results were still positive at 1:100 and 1:30 dilutions, respectively. However, for NC, a lower dilution (8:10) was required for a seropositive result. This study indicates that, at herd-level, the use of pooled serum is a useful strategy for monitoring infectious diseases (BVD, IBR and EBL) but not NC, using readily available diagnostic assays.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cytogenetic markers to understand chromosome diversification and conflicting taxonomic issues in Rineloricaria (Loricariidae: Loricariinae) from Rio Grande do Sul coastal drainages - Natália Bortholazzi Venturelli; Fabio Hiroshi Takagui; Luis Ricardo Santana Pompeo; Mônica Sônia Rodriguez; Renata da Rosa; Lucia Giuliano-Caetano (Biologia, 2021)

Phylogeographic analysis of foot‐and‐mouth disease virus serotype O dispersal and associated drivers in East Africa - Anna Munsey; Frank Norbert Mwiine; Sylvester Ochwo; Lauro Velazquez‐Salinas; Zaheer Ahmed; Francois Maree; Luis L. Rodriguez; Elizabeth Rieder; Andres Perez; Simon Dellicour; Kimberly VanderWaal (Molecular Ecology, 2021)
The continued endemicity of foot and mouth disease virus (FMDV) in East Africa has significant implications for livestock production and poverty reduction, yet its complex epidemiology in endemic settings remains poorly understood. Identifying FMDV dispersal routes and drivers of transmission is key to improved control strategies. Environmental heterogeneity and anthropogenic drivers (e.g., demand for animal products) can impact viral spread by influencing host movements. Here, we utilized FMDV serotype O VP1 genetic sequences and corresponding spatiotemporal data in order to (i) infer the recent dispersal history, and (II) investigate the impact of external factors (cattle density, human population density, proximity to livestock markets, and drought) on dispersal velocity, location, and direction of FMDV serotype O in East Africa. We identified statistical evidence of long‐distance transmission events, and we found that FMDV serotype O tends to remain circulating in areas of high cattle density, high human population density, and in close proximity to livestock markets. The latter two findings highlight the influence of anthropogenic factors on FMDV serotype O spread in this region. These findings contribute to the understanding of FMDV epidemiology in East Africa and can help guide improved control measures.

The SoNAP gene from sugarcane (Saccharum officinarum) encodes a senescence-associated NAC transcription factor involved in response to osmotic and salt stress - Evelyn A. Carrillo-Bermejo; Samuel David Gamboa-Tuz; Alejandro Pereira-Santana; Miguel A. Keb-Llanes; Enrique Castaño; Luis Joel Figueroa-Yañez; Luis C. Rodriguez-Zapata (Journal of Plant Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Iterative subtractive binning of freshwater chronoseries metagenomes identifies over 400 novel species and their ecologic preferences - Luis M. Rodriguez‐R; Despina Tsementzi; Chengwei Luo; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Recent advances in sequencing technology and bioinformatic pipelines have allowed unprecedented access to the genomes of yet‐uncultivated microorganisms from diverse environments. However, the catalogue of freshwater genomes remains limited, and most genome recovery attempts in freshwater ecosystems have only targeted specific taxa. Here, we present a genome recovery pipeline incorporating iterative subtractive binning, and apply it to a time series of 100 metagenomic datasets from seven connected lakes and estuaries along the Chattahoochee River (Southeastern USA). Our set of metagenome‐assembled genomes (MAGs) represents >400 yet‐unnamed genomospecies, substantially increasing the number of high‐quality MAGs from freshwater lakes. We propose names for two novel species: ‘ Candidatus Elulimicrobium humile’ (‘ Ca . Elulimicrobiota’, ‘Patescibacteria’) and ‘ Candidatus Aquidulcis frankliniae’ (‘Chloroflexi’). Collectively, our MAGs represented about half of the total microbial community at any sampling point. To evaluate the prevalence of these genomospecies in the chronoseries, we introduce methodologies to estimate relative abundance and habitat preference that control for uneven genome quality and sample representation. We demonstrate high degrees of habitat‐specialization and endemicity for most genomospecies in the Chattahoochee lakes. Wider ecological ranges characterized smaller genomes with higher coding densities, indicating an overall advantage of smaller, more compact genomes for cosmopolitan distributions.

Genome repository of oil systems: An interactive and searchable database that expands the catalogued diversity of crude oil‐associated microbes - Smruthi Karthikeyan; Luis M. Rodriguez‐R; Patrick Heritier‐Robbins; Janet K. Hatt; Markus Huettel; Joel E. Kostka; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Microbial communities ultimately control the fate of petroleum hydrocarbons (PHCs) that enter the natural environment, but the interactions of microbes with PHCs and the environment are highly complex and poorly understood. Genome‐resolved metagenomics can help unravel these complex interactions. However, the lack of a comprehensive database that integrates existing genomic/metagenomic data from oil environments with physicochemical parameters known to regulate the fate of PHCs currently limits data analysis and interpretations. Here, we curated a comprehensive, searchable database that documents microbial populations in natural oil ecosystems and oil spills, along with available underlying physicochemical data, geocoded via geographic information system to reveal their geographic distribution patterns. Analysis of the ~2000 metagenome‐assembled genomes (MAGs) available in the database revealed strong ecological niche specialization within habitats. Over 95% of the recovered MAGs represented novel taxa underscoring the limited representation of cultured organisms from oil‐contaminated and oil reservoir ecosystems. The majority of MAGs linked to oil‐contaminated ecosystems were detectable in non‐oiled samples from the Gulf of Mexico but not in comparable samples from elsewhere, indicating that the Gulf is primed for oil biodegradation. The repository should facilitate future work toward a predictive understanding of the microbial taxa and their activities that control the fate of oil spills.

Acute administration of levetiracetam in tonic pain model modulates gene expression of 5HT1A and 5HT7 receptors in the thalamus of rats (Rattus norvergicus) - José Luis Cortes-Altamirano; Samuel Reyes-Long; Herlinda Bonilla-Jaime; Denise Clavijo-Cornejo; Javier Vargas; Cindy Bandala; Alfonso Alfaro-Rodriguez (Molecular Biology Reports, 2020)

Diabetes and cardiovascular disease mortality among a population-based cohort of women with and without breast cancer - Luis A. Rodriguez; Patrick T. Bradshaw; Humberto Parada; Nikhil K. Khankari; Tengteng Wang; Rebecca J. Cleveland; Susan L. Teitelbaum; Alfred I. Neugut; Marilie D. Gammon (Cancer Causes & Control, 2020)

Comparative Study of the Degradation of the Diclofenac Drug Using Photo-Peroxidation and Heterogeneous Photocatalysis with UV-C and Solar Radiation - Dennis Díaz-Rodríguez; María Elena Palacios-Antón; Rayany Magali Da Rocha Santana; Luis Santiago Quiroz-Fernández; Yunet Gómez-Salcedo; Alex Leandro Andrade de Lucena; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz (Water, Air, & Soil Pollution, 2020)

CA19-9 capability as predictor of pancreatic cancer resectability in a Spanish cohort - Marta Herreros-Villanueva; Lourdes Ruiz-Rebollo; Mario Montes; Mario Rodriguez-Lopez; María Francisco; Joaquín Cubiella; Eduardo Iyo; Emilio Garabitos; Emma Martínez Moneo; Maider Martos; Enrique de Madaria; Ibon Martínez-Arránz; et al. (Molecular Biology Reports, 2020)

Deprescribing of non-antiretroviral therapy in HIV-infected patients - José-Ramón Blanco; Ramón Morillo; Vicente Abril; Ismael Escobar; Enrique Bernal; Carlos Folguera; Fátima Brañas; Mercedes Gimeno; Olatz Ibarra; José-Antonio Iribarren; Alicia Lázaro; Ana Mariño; et al. (European Journal of Clinical Pharmacology, 2020)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Lipotoxic Effects of Palmitic Acid on Astrocytes Are Associated with Autophagy Impairment - Ana Ortiz-Rodriguez; Estefania Acaz-Fonseca; Patricia Boya; Maria Angeles Arevalo; Luis M. Garcia-Segura (Molecular Neurobiology, 2019)

Contributions of Hydrology to Vesicular Stomatitis Virus Emergence in the Western USA - Emile Elias; D. Scott McVey; Debra Peters; Justin D. Derner; Angela Pelzel-McCluskey; T. Scott Schrader; Luis Rodriguez (Ecosystems, 2019)

Climate Change and Atlantic Multidecadal Oscillation as Drivers of Recent Declines in Coral Growth Rates in the Southwestern Caribbean - Luis D. Lizcano-Sandoval; Ángela Marulanda-Gómez; Mateo López-Victoria; Alberto Rodriguez-Ramirez (Frontiers in Marine Science, 2019)

Spatial distribution of Donax trunculus (Linnaeus, 1758) populations along the intertidal area of the Gulf of Cádiz (SW, Spain) - Sara Román; Raimundo Blanco. Pérez; Luis Silva; Ana Rodriguez-Rua; Miguel Cojan; Esperanza García; Marina Delgado (Frontiers in Marine Science, 2019)

Research and management as key drivers in the evolution of the fishery of striped venus (Chamelea gallina) in the Spanish waters of the Gulf of Cádiz - Luis Silva Caparro; Marina Delgado Fernández; Miguel Cojan Burgos; Ana Rodriguez-Rua Franch; Sara Román Romero; Raimundo Blanco Pérez; Esperanza García Sumariva; Alejandro Terrón Singler; Javier Collado Vallejo (Frontiers in Marine Science, 2019)

Reproductive and population aspects of Mactra stultorum (Linnaeus, 1758) in the littoral of Huelva (SW Spain) - Ana Rodriguez-Rua; Luis Silva; Miguel Cojan; Raimundo Blanco; Sara Roman; Esperanza García; Marina Delgado (Frontiers in Marine Science, 2019)

Analysis and damage assessment of discards in the hand dredge wedge clam fishery (Donax trunculus Linnaeus, 1758) in the Gulf of Cádiz (SW Spain - Raimundo Blanco; Sara Román; Ana Rodriguez-Rua; Miguel Coján; Luis Silva; Antonio Sánchez; Esperanza Lisa-García; Marina Delgado (Frontiers in Marine Science, 2019)

The fishery of the striped venus Chamelea gallina (Linnaeus, 1758) in the Spanish waters of the Gulf of Cadiz (SW Spain): distribution and abundance of target and commercial discarded species. - Miguel Cojan Burgos; Luis Silva Caparro; Ana Rodriguez-Rua Franch; Raimundo Blanco Pérez; Sara Roman Moreno; Esperanza Garcia Sumariva; Alejandro Garcia Gomez; MarinaL Delgado Fernández; Alejandro Terron Singler; Javier Collado Vallejo; Rafael Gálvez César; Francisco Morales Mazo (Frontiers in Marine Science, 2019)

Inflammatory and Anti-inflammatory Responses Co-exist Inside Lung Granuloma of Fatal Cases of Coccidioidomycosis: A Pilot Report - Heidi G. Rodriguez-Ramirez; Adolfo Soto-Dominguez; Gloria M. González; Oralia Barboza-Quintana; Mario C. Salinas-Carmona; Luis A. Ceceñas-Falcon; Roberto Montes-de-Oca-Luna; Alma Y. Arce-Mendoza; Adrian G. Rosas-Taraco (Mycopathologia, 2018)

Tibolone Reduces Oxidative Damage and Inflammation in Microglia Stimulated with Palmitic Acid through Mechanisms Involving Estrogen Receptor Beta - Oscar Hidalgo-Lanussa; Marco Ávila-Rodriguez; Eliana Baez-Jurado; Jairo Zamudio; Valentina Echeverria; Luis Miguel Garcia-Segura; George E. Barreto (Molecular Neurobiology, 2018)

Seismotectonics of south-west Dominican Republic using recent data - Javier Rodriguez; Jens Havskov; Mathilde Bøttger Sørensen; Luis Fernando Santos (Journal of Seismology, 2018)

Evidence of subclinical foot-and-mouth disease virus infection in young calves born from clinically recovered cow under natural condition - Rajeev Ranjan; Jitendra K. Biswal; Saravanan Subramaniam; Bana B. Dash; Karam P. Singh; Jonathan Arzt; Luis L. Rodriguez; Bramhadev Pattnaik (Tropical Animal Health and Production, 2018)

Influence of increasing temperature on the scorpion sting incidence by climatic regions - Magali Hurtado‐Díaz; José Guzmán‐Ontiveros; Luis A. Arias‐Medellín; Leticia Hernández‐Cadena; Grea L. Moreno‐Banda; Sandra L. Rodriguez‐Dozal; José L. Texcalac‐Sangrador; Pamela E. Zúñiga‐Bello; Horacio Riojas‐Rodríguez (International Journal of Climatology, 2018)
Scorpion stings are a major public health concern representing a frequent cause of intoxication in many countries. The present study aims to examine the impact of climate variability in different climatic regions of the state of Morelos in Mexico on the incidence of scorpion stings. An ecological study was conducted using a retrospective time‐series analysis. Weekly reported scorpion sting cases from the Unique System of Information for Epidemiological Surveillance (SUIVE) and daily temperature and precipitation from the National Meteorological Service were obtained from 1999 to 2007. The geographical region of study was divided according three climatic conditions into Hot region (HR), Warm region (WR) and Cold region (CR). Generalized Linear Models were used to estimate the percent change [95% confidence intervals (CI)] of scorpion sting cases associated to an increase of 1 °C of temperature and 1 cm of precipitation in each climatic region. During the period of study there were 281 076 scorpion sting cases reported in the State of Morelos, Mexico. Positive correlations among temperature and scorpion sting cases were found ( R = 0.59 and 0.70 in the HR and WR, respectively). Regions with the hottest temperatures had the greatest effect, showing a 9.8% (CI 95%: 8.30–11.30) increase in scorpion sting cases per 1 °C increased in temperature. Increase in minimum and maximum temperatures have a delayed effect on scorpion stings cases and these may vary by climatic region.

Higher In vitro Proliferation Rate of Rhizopus oryzae in Blood of Diabetic Individuals in Chronic Glycaemic Control Compared with Non-diabetic Individuals - Grace Salazar-Tamayo; Luis E. López-Jácome; Jesús Resendiz-Sanchez; Rafael Franco-Cendejas; Patricia Rodriguez-Zulueta; Dora E. Corzo-León (Mycopathologia, 2017)

Autonomous Coral Reef Survey in Support of Remote Sensing - Steven G. Ackleson; Joseph P. Smith; Luis M. Rodriguez; Wesley J. Moses; Brandon J. Russell (Frontiers in Marine Science, 2017)

L-Type Calcium Channels Modulation by Estradiol - Nelson E. Vega-Vela; Daniel Osorio; Marco Avila-Rodriguez; Janneth Gonzalez; Luis Miguel García-Segura; Valentina Echeverria; George E. Barreto (Molecular Neurobiology, 2017)

Arc-seamount collision: driver for vertical-axis rotations in Azuero, Panama - Luis A. Rodriguez-Parra; Camilo Gaitán; Camilo Montes; Germán Bayona; Augusto Rapalini (Studia Geophysica et Geodaetica, 2017)

Life History and Mating Behavior of Rhagoletis solanophaga (Diptera: Tephritidae), a Non-Diapausing Species with Highly Variable Mating Duration - Juan Rull; Solana Abraham; Eduardo Tadeo; Christian Luis Rodriguez (Journal of Insect Behavior, 2016)

Experimental and DFT characterization, antioxidant and anticancer activities of a Cu(II)–irbesartan complex: structure–antihypertensive activity relationships in Cu(II)–sartan complexes - María S. Islas; Alicia Luengo; Carlos A. Franca; Mercedes Griera Merino; Laura Calleros; Manuel Rodriguez-Puyol; Luis Lezama; Evelina G. Ferrer; Patricia A. M. Williams (JBIC Journal of Biological Inorganic Chemistry, 2016)

Investigating PPCP Removal from Wastewater by Powdered Activated Carbon/Ultrafiltration - Elena Rodriguez; Margarida Campinas; Juan Luis Acero; Maria João Rosa (Water, Air, & Soil Pollution, 2016)

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz - José L. Rueda; Emilio González-García; Cinja Krutzky; Francisco J. López-Rodriguez; Gerardo Bruque; Nieves López-González; Desiree Palomino; Ricardo F. Sánchez; Juan Tomás Vázquez; Luis M. Fernández-Salas; Victor Díaz-del-Río (Marine Biodiversity, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Gluten ataxia is better classified as non-celiac gluten sensitivity than as celiac disease: a comparative clinical study - Luis Rodrigo; Carlos Hernández-Lahoz; Eugenia Lauret; Maria Rodriguez-Peláez; Miroslav Soucek; Rachele Ciccocioppo; Peter Kruzliak (Immunologic Research, 2016)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Effects of isometric training on the knee extensor moment–angle relationship and vastus lateralis muscle architecture - Luis M. Alegre; Asunción Ferri-Morales; Raúl Rodriguez-Casares; Xavier Aguado (European Journal of Applied Physiology, 2014)

Theiler’s virus infection provokes the overexpression of genes coding for the chemokine Ip10 (CXCL10) in SJL/J murine astrocytes, which can be inhibited by modulators of estrogen receptors - Nazario Rubio; Maria-Angeles Arevalo; Marie Cerciat; Francisco Sanz-Rodriguez; Mikko Unkila; Luis Miguel Garcia-Segura (Journal of NeuroVirology, 2014)

Do Cloud Properties in a Puerto Rican Tropical Montane Cloud Forest Depend on Occurrence of Long-Range Transported African Dust? - Johanna K. Spiegel; Nina Buchmann; Olga L. Mayol-Bracero; Luis A. Cuadra-Rodriguez; Carlos J. Valle Díaz; Kimberly A. Prather; Stephan Mertes; Werner Eugster (Pure and Applied Geophysics, 2014)

Evaluation of Mangrove Cover Changes in Mexico During the 1970–2005 Period - Luis Valderrama; Carlos Troche; Ma. Teresa Rodriguez; Daniel Marquez; Berenice Vázquez; Samuel Velázquez; Alma Vázquez; Ma. Isabel Cruz; Rainer Ressl (Wetlands, 2014)

Crambescidin 816 induces calcium influx though glutamate receptors in primary cultures of cortical neurons - Martín Vázquez Víctor; Vale González Carmen; Bondu Stéphanie; Thomas Olivier; Rodriguez Vieytes Mercedes; Botana López Luis (Frontiers in Marine Science, 2014)

Technical and Economic Analysis of Aeroponics and other Systems for Potato Mini-Tuber Production in Latin America - Julian R. Mateus-Rodriguez; Stef de Haan; Jorge L. Andrade-Piedra; Luis Maldonado; Guy Hareau; Ian Barker; Carlos Chuquillanqui; Victor Otazú; Rebeca Frisancho; Carolina Bastos; Arione S. Pereira; Carlos A. Medeiros; et al. (American Journal of Potato Research, 2013)

Elucidating the function of ejaculate expulsion and consumption after copulation by female Euxesta bilimeki - Christian Luis Rodriguez-Enriquez; Eduardo Tadeo; Juan Rull (Behavioral Ecology and Sociobiology, 2013)

Full-length genome analysis of vesicular stomatitis New Jersey virus strains representing the phylogenetic and geographic diversity of the virus - Steven J. Pauszek; Luis L. Rodriguez (Archives of Virology, 2012)

Epitope selection for multipeptide proteins: the case of RNA polymerase IV and V - Leydi de Rocio Canche Moo; Analy Arroyo Herrera; Luis Rodriguez-Zapata; Victor Suarez; Enrique Castano (Biologia, 2012)

New polymorphisms in human MEF2C gene as potential modifier of hypertrophic cardiomyopathy - Cristina Alonso-Montes; Manuel Naves-Diaz; Jose Luis Fernandez-Martin; Julian Rodriguez-Reguero; Cesar Moris; Eliecer Coto; Jorge B. Cannata-Andia; Isabel Rodriguez (Molecular Biology Reports, 2012)

Evaluation of the criteria to identify single-fibre potentials in human muscle fibres - Javier Rodriguez-Falces; Luis Gila; Nonna Alexandrovna Dimitrova (Biological Cybernetics, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Influence of the shape of intracellular potentials on the morphology of single-fiber extracellular potentials in human muscle fibers - Javier Rodriguez-Falces; Javier Navallas; Luis Gila; Armando Malanda; Nonna Alexandrovna Dimitrova (Medical & Biological Engineering & Computing, 2012)

Genetic and antigenic relationships of vesicular stomatitis viruses from South America - Steven J. Pauszek; Jose del C. Barrera; Tony Goldberg; Rossana Allende; Luis L. Rodriguez (Archives of Virology, 2011)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

Multi-level modelling of chlorination by-product presence in drinking water distribution systems for human exposure assessment purposes - Christelle Legay; Manuel J. Rodriguez; Luis Miranda-Moreno; Jean-Baptiste Sérodes; Patrick Levallois (Environmental Monitoring and Assessment, 2011)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Nitrogen-Use Efficiency in Relation to Different Forms and Application Rates of Se in Lettuce Plants - Juan J. Ríos; Begoña Blasco; Luis M. Cervilla; Maria M. Rubio-Wilhelmi; Miguel A. Rosales; Eva Sanchez-Rodriguez; Luis Romero; Juan M. Ruiz (Journal of Plant Growth Regulation, 2010)

Role of cannabis and endocannabinoids in the genesis of schizophrenia - Emilio Fernandez-Espejo; Maria-Paz Viveros; Luis Núñez; Bart A. Ellenbroek; Fernando Rodriguez de Fonseca (Psychopharmacology, 2009)

Comparative evaluation of motor unit architecture models - Javier Navallas; Armando Malanda; Luis Gila; Javier Rodriguez; Ignacio Rodriguez (Medical & Biological Engineering & Computing, 2009)

Herbivore-Induced Volatiles in the Perennial Shrub, Vaccinium corymbosum, and Their Role in Inter-branch Signaling - Cesar R. Rodriguez-Saona; Luis E. Rodriguez-Saona; Christopher J. Frost (Journal of Chemical Ecology, 2009)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Analysis of HLA class I expression in progressing and regressing metastatic melanoma lesions after immunotherapy - Rafael Carretero; José M. Romero; Francisco Ruiz-Cabello; Isabel Maleno; Felix Rodriguez; Francisco M. Camacho; Luis M. Real; Federico Garrido; Teresa Cabrera (Immunogenetics, 2008)

Characterization of the full-length genomic sequences of vesicular stomatitis Cocal and Alagoas viruses - Steven J. Pauszek; Rossana Allende; Luis L. Rodriguez (Archives of Virology, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

Field surveys for potential ozone bioindicator plant species in Argentina - Chris Bergweiler; Hebe Carreras; Eduardo Wannaz; Judith Rodriguez; Beatriz Toselli; Luis Olcese; Maria Luisa Pignata (Environmental Monitoring and Assessment, 2008)

FXTAS in Spanish Patients with Ataxia: Support for Female FMR1 Premutation Screening - Laia Rodriguez-Revenga; Beatriz Gómez-Anson; Esteban Muñoz; Dolores Jiménez; Monica Santos; Mar Tintoré; Gisela Martín; Luis Brieva; Montserrat Milà (Molecular Neurobiology, 2007)

Integrated control of Boophilus microplus ticks in Cuba based on vaccination with the anti-tick vaccine Gavac TM - Manuel Rodriguez Valle; Luis Mèndez; Mario Valdez; Miguel Redondo; Carlos Montero Espinosa; Milagro Vargas; Ricardo Lleonart Cruz; Humberto Perez Barrios; Guillermo Seoane; Emerio Serrano Ramirez; Oscar Boue; Jorge Lodos Vigil; et al. (Experimental and Applied Acarology, 2004)

Integrated control of Boophilus microplus ticks in Cuba based on vaccination with the anti-tick vaccine Gavac TM - Manuel rodriguez Valle; Luis Mèndez; Mario Valdez; Miguel Redondo; Carlos montero Espinosa; Milagro Vargas; Ricardo lleonart Cruz; Humberto perez Barrios; Guillermo Seoane; Emerio serrano Ramirez; Oscar Boue; Jorge lodos Vigil; et al. (Experimental and Applied Acarology, 2004)

FEEDING ECOLOGY OF THE MARINE OTTER ( LUTRA FELINA ) IN A ROCKY SEASHORE OF THE SOUTH OF CHILE - Gonzalo Medina‐Vogel; Claudio Delgado Rodriguez; P. Ricardo E. Alvarez; V. Jose Luis Bartheld (Marine Mammal Science, 2004)
A bstract The marine otter ( Lutra felina ) lives exclusively along exposed rocky shorelines on the South American Pacific coast from Peru (6°S), to Cape Horn, Chile (56°S), and Isla de los Estados, Argentina. L. felina diet and its relationship to prey availability and energy content was assessed by spraint and prey remains analysis, direct observation, and the use of crab pots and fish traps, at four sites on the Valdivian coast in the south of Chile, between June 1999 and June 2000. Based on spraints analysis, the diet was composed of 25 species; 52% (13/25) of the species identified were crustaceans, 40% (10/25) were fish, and 8% (2/25) were mollusks. Crustaceans were found in 78% of 475 spraints, 100% of 929 prey remains, and 90.8% of prey determined by direct observation, fish in 20% of spraints and 9.0% of prey determined by direct observation, and mollusks in 2% of spraints and 0.2% of prey determined by direct observation. Observed seasonal variation in prey availability was reflected in the otter diet. Fourteen prey species were trapped; 43% (6/14) were crustaceans and 57% (8/14) fish, crustaceans were 93% of 566 trapped individuals, fish 7%. L. felina showed opportunistic feeding behavior, selecting prey seasonally according to their availability rather than to their energy input.

Host suitability of the New World stalkborer Diatraea considerata for three Old World Cotesia parasitoids - Robert N. Wiedenmann; J.W. Smith; Luis A. Rodriguez-del-Bosque (BioControl, 2003)

Volatile Emissions Triggered by Multiple Herbivore Damage: Beet Armyworm and Whitefly Feeding on Cotton Plants - Cesar Rodriguez-Saona; Steven J. Crafts-Brandner; Luis A. Cañas (Journal of Chemical Ecology, 2003)

Estimation of coancestry in Iberian pigs using molecular markers - Miguel Toro; Carmen Barragán; Cristina Óvilo; Jaime Rodrigañez; Carmen Rodriguez; Luis Silió (Conservation Genetics, 2002)

Genealogical Analysis of a Closed Herd of Black Hairless Iberian Pigs - Miguel A. Toro; Jaime Rodriganez; Luis Silio; Carmen Rodriguez (Conservation Biology, 2000)

Genealogical Analysis of a Closed Herd of Black Hairless Iberian Pigs - Miguel A. Toro; Jaime Rodrigañez; Luis Silio; Carmen Rodriguez (Conservation Biology, 2000)
Livestock breeds are recognized as important components of world biodiversity. The Iberian pig is a swine breed well adapted to the Mediterranean forest ecosystem and provides cured products of high quality. The ancient population of Iberian pigs ( Sus scrofa meridionalis ) was differentiated in several local types, the black hairless pigs representing the fattest genetic type. The conservation program of the Guadyerbas strain has maintained this germplasm isolated since 1945 as a closed population in an experimental herd. The complete pedigree, with 1000 breeding animals descending from 24 founders, has been used to measure along the successive cohorts of breeding animals the effective number of founders, effective number of nonfounders, founder genome equivalents, and expected number of founders' surviving alleles. For the last cohort, the values were 10.34, 1.42, 1.25, and 4.06, respectively. The evolution of inbreeding and coancestry and its components attributable to each founder were also studied. The rate of increase in inbreeding and coancestry was 2.21% per cohort, or 0.906% per year. Finally, the effect of family structure and mating tactics on the evolution of coancestry was also analyzed. The greatest rates of coancestry per cohort were attributable to unbalanced family sizes, and the use of minimum coancestry matings effectively delayed the increase in inbreeding.

A novel germline mutation in exon 5 of the multiple endocrine neoplasia type 1 gene - A. Chico; Luis Gallart; Eugenia Mato; Carmen Mayoral; Jesus M. Martin-Campos; Lluís Catasús; Jose Rodriguez-Espinosa; Xavier Matías-Guiu; Francisco Blanco-Vaca; Alberto de Leiva (Journal of Molecular Medicine, 1998)

Influence of potato composition on chip color quality - Luis E. Rodriguez-Saona; Ronald E. Wrolstad (American Journal of Potato Research, 1997)

Experimental release of an Iberian lynx (Lynx pardinus) - Alejandro Rodriguez; Luis Barrios; Miguel Delibes (Biodiversity and Conservation, 1995)

Effect of anticalmodulin drugs on the action of yeast ? factor pheromone - Teresa Ruiz; Luis Rodriguez (Archives of Microbiology, 1986)